2006
DOI: 10.1590/s1413-82712006000100003
|View full text |Cite
|
Sign up to set email alerts
|

Transtorno de estresse pós-traumático e funções cognitivas

Abstract: ResumoO Transtorno de Estresse Pós-Traumático (TEPT) é um transtorno prevalente, associado a alterações neurobioló-gicas e cognitivas. O presente artigo é um estudo teórico sobre as aplicações da avaliação neuropsicológica no TEPT. Inicialmente são revisados aspectos conceituais do transtorno, bem como alterações neurobiológicas relacionadas aos prejuízos cognitivos comumente detectados. Finalmente, argumenta-se que a avaliação dos prejuízos nas funções de memória, atenção e, sobretudo, funções executivas são … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0
13

Year Published

2010
2010
2017
2017

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 32 publications
0
5
0
13
Order By: Relevance
“…Some studies have found associations between exposure to such events and a higher incidence of mood disturbances (Boardman, Alexander, & Stallings, 2011;Reyes-Rodríguez, Rivera-Medina, Cámara-Fuentes, Suárez-Torres, & Bernal, 2013). Studies suggest that 60 to 90 percent of the general population has been exposed to at least one financial, family, social, or psychological stressful event, and considers the event to have been traumatic (Breslau et al, 1998;Kristensen, Parente, & Kaszniak, 2005). Among students, the likelihood of exposure to a stressful situation may range from 10 to 90 percent depending on the type of event considered (Agustini, Asniar, & Matsuo, 2011;Smyth, Hockemeyer, Heron, Wonderlich, & Pennebaker, 2008;Yeager, Lee, & Jamieson, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have found associations between exposure to such events and a higher incidence of mood disturbances (Boardman, Alexander, & Stallings, 2011;Reyes-Rodríguez, Rivera-Medina, Cámara-Fuentes, Suárez-Torres, & Bernal, 2013). Studies suggest that 60 to 90 percent of the general population has been exposed to at least one financial, family, social, or psychological stressful event, and considers the event to have been traumatic (Breslau et al, 1998;Kristensen, Parente, & Kaszniak, 2005). Among students, the likelihood of exposure to a stressful situation may range from 10 to 90 percent depending on the type of event considered (Agustini, Asniar, & Matsuo, 2011;Smyth, Hockemeyer, Heron, Wonderlich, & Pennebaker, 2008;Yeager, Lee, & Jamieson, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…16,28,29 These alterations can affect emotional, behavioral regulation and cognitive processes, interfering with the normal psychopathological course. 22,23 The Posttraumatic Cognitions Inventory instrument, in its original and adapted versions, takes Foa et al's 15 'Emotional Processing Theory' as its theoretical reference. Traumatic events produce changes in the victims cognition of traumatic events, 13,14 which plays an important role in later emotional responses.…”
Section: Introductionmentioning
confidence: 99%
“…Essa desordem já está sendo considerada uma das doenças que mais causa prejuízo funcional na vida dos indivíduos, pois os impede de enfrentar locais e situações que causam extremo medo e ansiedade (Kristensen et al, 2006).…”
Section: Introductionunclassified
“…As pesquisas atuais (Kessler et al, 2005;Kristensen et al, 2006) apontam para o fato de que grande parte das pessoas vivenciou, vai vivenciar ou tem contato com alguém que experienciou ao menos um evento traumático ao longo da vida. De fato, há estudo que indica que entre 60 e 80% dos indivíduos na população geral vai passar por alguma situação estressora potencialmente traumática (Kristensen et al, 2006).…”
Section: Introductionunclassified
See 1 more Smart Citation